How does income inequality affect energy rebound effect? Empirical evidence from China - Maliyamu Abudureheman; Nadira Ablimit; Yuanqi Zhou (Sustainable Futures)
Reducing income inequality and controlling energy rebound are both important targets of the Sustainable Development Goals (SDGs). When we strive for realizing these goals, is there a win-win result between them or a trade-off? Nevertheless, these important questions often be ignored in the previous literatures. To fill this research gap, we carry out a systematic exploration of the nexus between income inequality and energy rebound effect based on a panel dataset from China. The research findings indicate that income inequality has a negative impact on the energy rebound effect, in other words, there exists a tradeoff between income inequality and energy rebound. The economic mechanism investigation based on different income groups (i.e., the top 25 %, upper-middle 25 %, lower-middle 25 %, and the lowest 25 % income groups) further illustrates the negative nexus between income inequality and energy rebound. Additionally, the two-step quantile regression results indicate that there exist asymmetric effects of income inequality and other influencing factors on energy rebound. Besides, the impact of income inequality on energy rebound has obvious regional heterogeneity; To be specific, income inequality positively affect energy rebound in the eastern region, while it exhibits a negative impact in the central and western regions.